Applications and advances of CRISPR/Cas9 in animal cancer model. (3rd March 2020) - Xu, Min; Weng, Qiaoyou; Ji, Jiansong
Abstract: The recent developments of clustered regularly interspaced short palindromic repeats(CRISPR)/-associate protein 9 (CRISPR/Cas9) have got scientific interests due to the straightforward, efficient and versatile talents of it. Furthermore, the CRISPR/Cas9 system has democratized access to gene editing in many biological fields, including cancer. Cancer development is a multistep process caused by innate and acquired mutations and leads to the initiation and progression of tumorigenesis. It is obvious that establishing appropriate animal cancer models which can simulate human cancers is crucial for cancer research currently. Since the emergence of CRISPR/Cas9, considerable efforts have been taken by researchers to apply this technology in generating animal cancer models. Although there is still a long way to go we are happy to see the achievements we have made and the promising future we have.